2020
DOI: 10.1111/and.13913
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness ofHedyotis diffusaWilld extract in a mouse model of experimental autoimmune prostatitis

Abstract: The National Institutes of Health (NIH) Category III Prostatitis, also known as chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), remains an enigma for many patients and practitioners. According to the leucocytes' presence in prostatic secretions, CP/CPPS is sub-classified as NIH category III-A (inflammatory type) and NIH category III-B (noninflammatory type) (Krieger et al., 1999). Overall, it has been assessed that 4.5%-9% of men in elderly patients have been diagnosed with prostatitis, and the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…HDW is also a well-known TMC with a variety of activities, especially its anticancer effect in the clinic [ 24 ]. The latest study demonstrated that HDW significantly reduced inflammatory lesion and inflammatory cell infiltration in a mouse model of experimental autoimmune prostatitis [ 25 ]. In addition, HDW as a complementary therapy is important for the treatment of advanced nasopharyngeal carcinoma patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDW is also a well-known TMC with a variety of activities, especially its anticancer effect in the clinic [ 24 ]. The latest study demonstrated that HDW significantly reduced inflammatory lesion and inflammatory cell infiltration in a mouse model of experimental autoimmune prostatitis [ 25 ]. In addition, HDW as a complementary therapy is important for the treatment of advanced nasopharyngeal carcinoma patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wazir et al showed that the water extract of H. diffusa effectively improved the urination symptoms, relieved pain, and enhanced the inflammatory response in an experimental autoimmune prostatitis mouse model, which might be mediated by the downregulation of the proinflammatory factor TNF-α. [31] The two abovementioned Chinese medicines both have catharsis effects. In addition, red ginseng is beneficial to the Qi and blood, strengthening the heart and spleen, and is often used in patients with deficiency syndrome.…”
Section: Acupuncture Therapymentioning
confidence: 99%
“…These therapies have proven efficacies in treating urological disorders (Moran et al, 2013), but the outcomes in UCPPS patients are variable. While there are several animal studies suggesting the potential benefits of herbal therapies for IC/BPS treatment (Cui et al, 2020;Tokita et al, 2023;Wazir et al, 2021;, there were only a few well-designed clinical trials with appropriate controls and sample sizes to provide definitive conclusions about their therapeutic effects. Therefore, future translational and clinical research on the mechanisms of the herbal substances' action and their efficacy for UCPPS patients is warranted (Dashdondov et al, 2021).…”
Section: Botulinum Toxin a (Botn-a) Injections In The Urinary Bladder...mentioning
confidence: 99%